Zarządzanie na styku kultur - strategie działania w obliczu szoku kulturowego - Stańczyk, Sylwia (Multicultural management - strategies in the face of cultural shock, 2006)
The main purpose of this article is to show basic problems of culture diversity managing. The author tries to answer the following question: what strategy of culture changes is appropriate in the face of companies’ culture diversity. The issues, considerations and conclusions showed in this paper are made with the support of literaturę studies, results of an empirical research and the author’s own experience.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 416-422